Mixed bacterial septicaemia in a bearded dragon (Pogona vitticeps) - Mazlan, Mazlina; Zakaria, Muhamad Alif (2019)
A 3-year-old, male, bearded dragon (Pogona vitticeps) was sent for necropsy to Veterinary Post Mortem Laboratory, Faculty of Veterinary Medicine, Universiti Putra Malaysia with a history of two days anorexia and watery faeces. Necropsy was conducted and organ samples were sent for bacterial isolation, as well as histopathology. At necropsy, the carcass was in fair body condition with minimal visceral and subcutaneous fat stores. The eyes were sunken with pale and dry skin. There was generalized severe congestion of the right lung, which was slightly dilated and contained thick, purulent exudate mixed with blood. Liver and kidneys were moderately congested. Detailed histopathologic investigation of the lung revealed severe mixed mononuclear and granulocytic inflammation. Marked vascular congestion with presence of exudates which consisted of eosinophilic proteinaceous coagulum mixed with heterophils in the air passageways. The exudates expanded the interstitium and lower airway. Proteus mirabilis, Morganella morganii, and Klebsiella pneumonia were isolated from the lung, liver and kidney samples. In consideration of the macroscopic, histological findings and bacterial isolation, the bearded dragon was diagnosed to have died of a mixed bacterial septicaemia. Infectious agents are a major disease problem among reptiles, with bacterial infections being responsible for the majority of morbidity and mortality of cases, and commonly causing septicaemia.